P726 Effectiveness of vedolizumab therapy in a real-world setting in Germany: First results of the VEDOibd study comparing vedolizumab to the use of other biologics. (15th January 2020) - Bokemeyer, B; Plachta-Danielzik, S; Sobotzki, C; Mohl, W; Hoffstadt, M; Krause, T; Atreya, R; von der Ohe, M; Graefe, U; Trentmann, L; Eisold, M; Linde, A; et al.
Abstract: Background: The VEDOibd I study is an investigator initiated, ongoing, non-interventional trial on biologics in IBD-patients (Crohn′s disease (CD) and ulcerative colitis (UC)) in Germany with consecutive recruitment and prospective documentation of effectiveness in induction and maintenance therapy of biologics, especially vedolizumab (VEDO). The aim of this analysis was to compare steroid-free remission rates in CD- and UC-patients after a 14-week-long induction phase of VEDO (bio-naïve and bio-experienced) vs. other biologics (infliximab (IFX), adalimumab (ADA), Golimumab (GLM), Ustekinumab (UST)) in bio-naïve patients. Methods: From 10/2017 to 07/2019 750 IBD-patients (CD: 414; UC: 336) from 45 gastroenterology practices and hospitals with IBD-experience from all over Germany were recruited in the VEDOibd I study of whom 232 CD- and 184 UC-patients completed induction phase (week 14) in this interim analysis. At week 14 we compared clinical response (CD: reduction of Harvey Bradshaw Index [HBI] from baseline to week 14 by >3 points or HBI < 4 in week 14; UC: reduction of partial Mayo score [pMayo] from baseline to week 14 by >3 points or a reduction of at least 30% compared with baseline) and steroid-free remission rates (CD: HBI < 4 and no systemic use of steroids or budesonide at week 14; UC: pMayo ≤1 plus a bleeding subscore = 0 and no systemic use of steroids or budesonide at week 14) in patients with VEDO vs. other biologics. Results: Ninety-two CD- and 111 UC-patients started a first-time VEDO therapy; of these 40 CD- (43%) and 57 UC-patients (51%) were bio-naïve. Furthermore 140 CD-patients (IFX 48.6%; ADA 47.1%; UST 4.3%) and 73 UC-patients (IFX 58.9%; ADA 24.7%; GLM 16.4%) started treatment with another biologic than VEDO and all of these were bio-naïve. Baseline characteristics were well balanced between both naïve groups (VEDO/other biologics; p > 0.05): males [%]: CD 38/41, UC 37/51; age [years]: CD 46 ± 15/42 ± 15, UC 43 ± 19/39 ± 15; disease duration [years]: CD 15 ± 11/9 ± 11, UC 9 ± 9/6 ± 7; extraintestinal manifestations [%]: CD 23/20, UC 7/15. Response/steroid-free remission rates after induction phase in biologic-naïve patients with VEDO and other biologics were 74.4%/57.5% vs. 78.4%/64.3% in CD (p>0.05) and 60.0%/21.1% vs. 56.0%/13.7% in UC (p>0.05), respectively. Conclusion: In this real-world setting we could show that in CD the effectiveness of VEDO vs. other biologics was very similar in bio-naïve patients and that in UC patients, VEDO treatment tended to be numerically superior to other biologics with respect to response and steroid-free remission rates. Further follow-up data of this interim-analysis including the whole planned study population of 1.200 IBD-patients will be shown in the near future.